2018
DOI: 10.1111/scs.12627
|View full text |Cite
|
Sign up to set email alerts
|

The caregiving phenomenon and caregiver participation in dementia

Abstract: Background Dementia presents barriers to the collaboration between individuals and the healthcare system. Caregivers perform multiple functions helping patients with basic and instrumental activities but also communicating and mediating the dyads’ needs within the broader social group. Interventions focusing on caregivers show that caregiver burden can be reduced, improving patient outcomes in a cost‐effective way, but the generalisation of these findings is limited by several factors such as low participation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 48 publications
1
33
0
1
Order By: Relevance
“…In this sense, the results of this study confirm the social tendency observed in southern Europe countries, namely that women generally assume a greater responsibility in the care of children, partners, and dependent family members [37]. Our analysis supports the fact that, in the family context, caring is almost exclusively considered to be a female role [39,40].…”
Section: Discussionsupporting
confidence: 86%
“…In this sense, the results of this study confirm the social tendency observed in southern Europe countries, namely that women generally assume a greater responsibility in the care of children, partners, and dependent family members [37]. Our analysis supports the fact that, in the family context, caring is almost exclusively considered to be a female role [39,40].…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, as reported in prior studies, the caregivers described how caring for their family member was associated with positive feelings, such as wellbeing or satisfaction [20,45], which contributes toward creating a positive and pleasant care environment and, in turn, promotes the involvement of caregivers in the process of SDM. This process is also perceived as being a psychological strategy toward facing the illness [46], helping to decrease the caregiver’s burden [47,48].…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, this research shows that having a low educational level can affect patients’/caregivers’ active participation in the process of SDM [40,50]. Therefore, it is especially important to train patients and their caregivers in competencies related to the management of health [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has been dedicated to family caregiving of people living with dementia, with a special focus on the correlation between caregiver burden and health outcomes , as well as between caregiver burden and their old relative's residential home placement . There has also been a research interest in the correlation between patient participation in relation to caregiver participation in dementia care . Some studies draw attention to how family care partners deal with the issue of recognising risks of incidents, problems and needs and how they require collaboration with formal care at different stages of dementia .…”
Section: Introductionmentioning
confidence: 99%